On the mass, heat and moisture balance in the field of monsoon depressions (MAUSAM, 1983)
Based on data of 27 monsoon depressions which formed in the Bay of Bengal during the two typical monsoon months, i.e., July and August and moved in the customary westerly to westnorthwesterly direction, mean lateral transports of mass, sensible heat and latent heat and moisture have been calculated. Distribution of depths of inflow and outflow layers with distance from the depression centre has been obtained. Vertical fluxes of the total effective energy including the transfers from the underlying surface are estimated. Magnitude of energy loss from the top of the depression field have been obtained and compared with what may be expected from the black body radiation at the cirrus level. Theoretically possible extent of rise of the convective elements from the surface heat supply, rising exclusively out of buoyancy forces has been determined. Heat sources and sinks, their areal extent, the rate of descent and the amount of evaporation the subsiding airmass would evaporate from the surface have been obtained and discussed. Maximum amounts of rainfall that could occur on the assumption that all converging moisture precipitates out, has been obtained for different distances from the depression centre. Frictional loss horizontal due to skin friction at the boundary layer has been computed and expressed in terms of the net sea level effective heat as well as the latent heat gained within the depression.